THE ROLE OF REAL ESTATE LEASE AGREEMENTS IN THE DEVELOPMENT OF ISLAMIC LAW - Saidakramov Saidazimxon Saidakbar o‘g‘li (Modern American Journals, 2025)
This study examines the pivotal role of real estate lease agreements in the development and modernization of Islamic law, focusing on their legal, ethical, and economic implications. Rooted in the Sharia principle of ijarah (leasing), these agreements have historically provided a framework for regulating property rights, ensuring fairness, and promoting socio-economic justice. The research traces the evolution of lease agreements from early Islamic jurisprudence to their contemporary applications in Islamic finance, illustrating how they have adapted to diverse socio-economic contexts while maintaining fidelity to core Islamic values. Through a comprehensive analysis of primary sources and modern case studies, the paper explores how lease agreements contribute to the codification of Islamic property law, the prevention of riba (usury) and gharar (uncertainty), and the promotion of equitable wealth distribution. Additionally, it highlights the growing relevance of ijarah-based instruments, such as Sukuk (Islamic bonds), which integrate real estate assets into global financial systems while preserving Sharia compliance. The findings underscore that real estate lease agreements not only serve as instruments of lawful property exchange but also function as catalysts for economic stability, social welfare, and the advancement of Islamic jurisprudence. This multidimensional role situates leasing as a cornerstone of both traditional Islamic law and contemporary Islamic finance, bridging the gap between classical jurisprudence and modern legal frameworks.
Keywords: Islamic law (Sharia), real estate lease agreements, Ijarah (Islamic leasing), Riba prohibition, islamic finance and Sukuk , socio-economic justice